Factors affecting customer experience for cellular mobile services of telecommunication companies in Kuala Terengganu / Wajihah Rashid - Rashid, Wajihah (Faculty of Business and Management, 2017)
Nowadays, telecommunication services providers offer many services regarding to telecommunication activities to their customers. Customer loyalty is related to the factors affecting customer experience for cellular mobile services subscriptions. This study aims in investigating what are the factors which determine customer experience in cellular mobile services of telecommunication companies. The factors including brand, price and service quality are analyzed as the independent variables and the dependent variable is customer experience. A systematic approach is developed by using descriptive study through structured questionnaires of data collection. Thus, customer experience is formulated as a conceptual framework for analysis in this study. The data are analyzed using descriptive analysis, reliability analysis, correlation analysis and multiple regression analysis. The result of regression analysis showed the significant factors that influenced customer experience are price and service quality provided by the telecommunication companies. In this study, it shows the most important factor is the price of cellular mobile services provided by the telecommunication companies. There are three recommendations given in this study. Firstly, future study is recommended to include other races of the respondents besides Malay such as Chinese and Indian respondents as well. Secondly, further study may include more independent variables. Thirdly, future study is proposed to emphasize the role of cellular service types (fixed and prepaid line) as an antecedent of engagement.